TIPOLOGI BAHASA BOLANGO DITINJAU DARI PEMBENTUKAN KATA - MUSA, DEWI YULIANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
Among many hundreds of languages ​​that exist in Indonesia, there are some languages ​​that are almost extinct and need serious attention. Bolangese, the subject of this study, is one example of these almost extinct languages, because of the number of speakers was predicted to be less than a thousand. This research proceedes from morphological types which consist of the process, rules and the types of word formation. Therefore, the aim of this research is to identify and explain the processes of word formation, determine the rules of word formation and explain the types of word formation. This research is qualitative by using method of descriptive linguistics which is describing the phenomena found in a language. Data source consisting of data written in the form of scripts of Bolangese were collected using the observation methods with the bibliographical technique and cooperation with informant technique. The technique of analyzing the data in this study was based on the distributional methods with the technique of binary opposition by Subroto (2007). Identification process and the rules of word formation of Bolangese have used the concept of Kridalaksana (1989), and for the analysis of language typology the concept from Keraf (1980) has been used. The result of this research show that the word formation through affixation in Bolangese comprises the following affixes; affixes forming verb, affixes forming nouns, forming adjectives, forming adverbs, and affixes forming imperative. However, the reduplication processes are forming verb, noun, adjective and adverb. The reduplication forming imperative has not yet been found. In Bolango language, rules for word formation itself consist of two types which are inflectional and derivational. Bolango language has a total of 44 types of word formation, consisting of 36 types of affixation and 8 types of reduplication. Thus, it can be concluded that Bolangese is a typical affixal and reduplicative language. Further research on Bolangese typology is suggested concerning other kinds of word formation, such as compositum, abbreviation and metaanalysis. Key Words : Bolangese Tipology Word Formation